From Swipe to Buy: Rethinking Digital Marketing Effectiveness through Social Media Advertising Features - Mavilinda, Hera Febria; Nailis, Welly; Putri, Yulia Hamdaini (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2026)
In an increasingly competitive digital marketplace, social media advertising features have become a central component of e-commerce marketing strategies. Despite their growing importance, empirical evidence on how these features influence purchase intention through brand-related constructs remains limited. This study examines the effect of social media advertising features on consumers' purchase intention, with brand awareness and brand trust as mediating variables. The Unified Theory of Acceptance and Use of Technology (UTAUT) is employed as the conceptual framework to explain the relationship between advertising features and purchase intention, as well as the mediating roles of brand awareness and brand trust. A quantitative approach with a causal research design was applied. Primary data were collected through an online questionnaire administered to 200 millennials and Gen Z who lived in Palembang City who actively use Instagram, follow Tokopedia's official account, and have been exposed to its advertisements. Data were analyzed using SEM with AMOS. The results show that social media advertising features significantly influence purchase intention, both directly and through brand trust, whereas brand awareness has no significant direct effect. These findings highlight the central role of brand trust in enhancing the effectiveness of social media advertising in technology-driven markets.